An Author’s Dilemma: Where to Publish? - Kafle, Raju (Medical Journal of Shree Birendra Hospital, 2020)
Journals are the essence of scholarly communication. They not only serve to disseminate latest scientific advancements but also provide a platform for archiving scholarly information for future reference, and allow a researcher to assert his or her scientific caliber. Selecting the most suitable journal to showcase one’s scholarly work is no mean feat. With more than 43,000 biomedical journals listed with PubMed1, the database maintained by United States National Library of Medicine (NLM), this exercise can easily baffle an inexperienced researcher. The huge risk of rejection of a paper from a journal that is not the right fit, and a widening web of dubious and predatory journals which publish almost everything sent to them, make this task particularly daunting. You may think that getting your paper into a journal with the highest possible impact factor is your only concern. However, this makes sense only if you think that you will be judged solely on the journal your paper is in rather than the quality and actual impact of the work. Although journal name and impact factor are still used to judge papers (or even researchers), the problems with this approach are becoming more widely known.2 Within one journal, papers can vary enormously in their quality and citations so it is unfair to judge a single paper by the mean number of citations in a whole journal.